Benzyl N '-(1H-indol-3-ylmethylidene)-hydrazinecarbodithioate - Khaledi, H.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2008)
The C(10)H(8)N(3)S(2) portion of the title molecule, C(17)H(15)N(3)S(3), is nearly planar (r.m.s. deviation 0.05 angstrom); this unit and the phenyl ring subtend an angle of 114.5 (2)degrees at the methylene C atom.